Studying the impact of academic mobility on intercultural competence: a mixed-methods perspective. Issue 3 (2nd July 2016) - Cots, Josep M.; Aguilar, Marta; Mas-Alcolea, Sònia; Llanes, Àngels
Abstract : This paper contributes to the study of the impact of academic mobility on the development of students' intercultural competence (IC). Following Byram, IC is seen as comprising the three components of knowledge, behaviour and attitude. The study adopts a mixed-methods approach, analysing the results of a quantitative pre-stay post-stay survey administered to 110 students from 2 universities in Catalonia (Spain), as well as one student's discursive construction of this impact during her study abroad (SA). The analysis explores the potential complementarity of the two perspectives. Findings show that for this group of students, SA of between 5 and 10 months had a stronger impact on the knowledge component of IC than on the behaviour and attitude components. The analysis of an individual student's experiential narratives is used to shed light on the challenge of personal 'change' in adapting to the 'difference' of the SA context.